Impact of wake modeling uncertainty on helicopter rotor aeroacoustic analysis - Vouros, S.; Goulos, I.; Scullion, C.; Nalianda, D.; Pachidis, V. (My University, 2019)
Free-wake models are routinely used in aeroacoustic analysis of helicopter rotors; however, their semi-empiricism is essentially accompanied with uncertainty related to physical wake parameters. In some cases, analysts have to resort to empirical adaption of these parameters based on previous experimental evidence. This paper investigates the impact of inherent uncertainty in wake aerodynamic modeling on the robustness of helicopter rotor aeroacoustic analysis. A free-wake aeroelastic rotor model is employed to predict high-resolution unsteady airloads, including blade-vortex interactions. A rotor aeroacoustics model, fundamentally based on Acoustic Analogy, is utilized to calculate aerodynamic noise in the time-domain. The individual analytical models are incorporated into a stochastic analysis numerical procedure, implemented through non-intrusive Polynomial Chaos expansion. The possible sources of uncertainty in wake tip-vortex core modeling are identified and their impact on noise predictions quantified. When experimental data to adjust the tip-vortex core model are not available the uncertainty in acoustic pressure and ground noise impact at observers dominated by blade-vortex interaction noise can reach up to 25% and 3.50 dB respectively. This work aims to devise generalized uncertainty maps to be used as modeling guidelines for aeroacoustic analysis in the absence of the robust evidence necessary for calibration of semi-empirical vortex core models.